The use of artificial intelligence in geography topics by university students an exploratory study derived from a master’s thesis - سعيد, آ.م.د. فؤاد خالد سعيد; نوری, آ.م.د. عادل محمد نوری; Omar, Avan Dilzar Khdir Omar (Sulaimani Journal for Humanities, 2025)
Artificial intelligence, a computer science field, develops system that mimic human intelligence by using machine learning in applications like robotics, data analysis, and voice assistants. This study aims to determine the level of artificial intelligence (AI) usage in geography subjects among students of the University of Sulaimani, the research community consists of male and female students from the first to fourth grades of the geography department in the colleges of (Basic Education, Humanitarians, and Humanities Education/ Said Sadiq) at the University of Sulaymaniyah, the study included (492) students from all four academic years. the research is quantitative research and used a descriptive method and the sample consisted of (255) students in all three colleges, the research used Scale to measure of (AI) usage, some results show that the level of (AI) usage in geography subjects was high overall from the students' perspective, and there were no statistically significant differences in the level of usage according to the variables of (gender and place of residence), the most important recommendations include training university teachers to use appropriate (AI) programs for students in geographical subjects.
Keywords: Artificial Intelligence; Geography; University Student